2020
DOI: 10.3390/life10110278
|View full text |Cite
|
Sign up to set email alerts
|

Macrobiont: Cradle for the Origin of Life and Creation of a Biosphere

Abstract: Although the cellular microorganism is the fundamental unit of biology, the origin of life (OoL) itself is unlikely to have occurred in a microscale environment. The macrobiont (MB) is the macro-scale setting where life originated. Guided by the methodologies of Systems Analysis, we focus on subaerial ponds of scale 3 to 300 m diameter. Within such ponds, there can be substantial heterogeneity, on the vertical, horizontal, and temporal scales, which enable multi-pot prebiotic chemical evolution. Pond size-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 156 publications
1
19
0
Order By: Relevance
“…Each of those would alter the steady state GP concentration. This is consistent with the idea suggested by Clark and Kolb [46] who discussed the possibility of various stages from abiotic synthesis to the possible origin of life to have happened in separate ponds or other sites that might be interconnected, and thus various multi-pot processes could potentially be mixed [47][48][49][50]. Hence, the GP produced under hot conditions was transferred to the water bodies with lower temperatures fairly quickly [46,[51][52][53][54] where it could then become incorporated into other prebiotic processes.…”
Section: Resultssupporting
confidence: 94%
“…Each of those would alter the steady state GP concentration. This is consistent with the idea suggested by Clark and Kolb [46] who discussed the possibility of various stages from abiotic synthesis to the possible origin of life to have happened in separate ponds or other sites that might be interconnected, and thus various multi-pot processes could potentially be mixed [47][48][49][50]. Hence, the GP produced under hot conditions was transferred to the water bodies with lower temperatures fairly quickly [46,[51][52][53][54] where it could then become incorporated into other prebiotic processes.…”
Section: Resultssupporting
confidence: 94%
“…The importance of this heterogeneity has been made especially clear with the discovery of molecular condensates, protein delimited compartments that function at many spatial scales within eukaryotic cells [ 45 ], with increasing focus now on prokaryotes [ 46 ]. The importance of spatial heterogeneity has also been noted in the discussion of the prebiotic generation of macromolecule precursors [ 47 , 48 , 49 , 50 ]. These observations lead to the supposition that spatial chemical inhomogeneity was continually present from the earliest phases of life’s development ( Table 1 , criterion 4).…”
Section: Systems Biology Criteriamentioning
confidence: 99%
“…We have demonstrated that it is possible to test the assumptions of laboratory simulations in prebiotic analogues of hydrothermal fields and hot springs. In the future, laboratory simulations should also take into account what we have learned from ancient hot springs that existed 3.5 billion years ago [ 13 ]. One such example is the Pilbara Craton of Western Australia [ 14 , 15 ], which has preserved both ancient hot spring mineral composition and fossilized stromatolites.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reactants we used are relatively resistant to oxidation, particularly for short exposures of hours, not years. A last variable to keep in mind is simply the size of the pools as discussed by Clark and Kolb [ 13 ]. For typical field experiments like those in Kamchatka, pools should range from half a liter to several liters in volume.…”
Section: Discussionmentioning
confidence: 99%